A Grow Together Project: Performance Evaluation of Improvised Organic Fertilizers on the Yield of Cash Crops and its Economic Contribution to Agriculture Graduates in Tawi-Tawi Province, Philippines - Puhagan, Edwin M (International Journal of Membrane Science and Technology, 2023)
This study considers improvised organic fertilizers as one of the bioremediation therapies to restore soil fertility and the ecological stability of the farming environment. This used four homemade materials and leftovers to create improvised organic fertilizers. Banana peels, papaya peels, leaves, fish remains, and sea urchin pines are common food wastes that typically have no further use after the food has been devoured. Farmers could use these materials in a bioremediation process that supports the farming environment’s ecological and economic stability. This study provides feedback on the significance of homemade organic fertilizer as it improves farmers’ economic and environmental contributions. The parameters of this study were the yields of these four crops and the farmer’s income. In this study, four different crops—peanut, bell pepper, string bean, and corn—were subjected to four different concentrations of improvised organic fertilizers, including: for the peanut, a concentrated mixture of ripe banana peels and papaya extract; for the bell pepper, a concentrated mixture of triturated sea urchin spines and basil extract; for the corn, a concentrated mixture of algae and wild basil extract; and for the string bean, a The data was analyzed using a Randomized Complete Block Design (RCBD), which produced highly good yield results for these crops and thus boosted the local farmers’ income. The results were as follows: 1) Peanuts treated with 1500ml improvised organic fertilizers yielded 3.06 kilograms with a total mean score of 3.59abc; 2) Bell peppers treated with 1500ml improvised organic fertilizers yielded 15.9 kilograms with a total mean score of 5.30; and 3) corn treated with 1500ml improvised organic fertilizers yielded 5.30 kilograms with a total mean score of 5.30. The farmers’ income was implied by the investment’s return on these four crops. According to the study, income grows when yield rises, and selling volume is high.